Translating Local Literature into English: A Workshop on Literary Translation for University Students - Hendra Sudarso; Yulian Purnama; Siswandi Siswandi (PT. Global Research Collaboration, 2025)
This community service project aimed to develop students’ translation competence while contributing to the preservation and internationalization of local literature. Implemented at Universitas 17 Agustus 1945 Banyuwangi, the project involved 26 English Language students in a three-month experiential program titled “Translating Local Literature into English.” The activities consisted of a translation workshop, fieldwork in Kemiren Village—a center of Osing culture—and the compilation of bilingual manuscripts. Students were trained in literary translation theory and techniques, then conducted field-based data collection, interviewing local elders and documenting oral texts. These texts were translated collaboratively, with the final outputs compiled into a bilingual anthology entitled “Echoes of Osing.”Survey results showed a significant increase in students’ translation skills and cultural awareness, with over 90% indicating improved confidence and understanding. The project also strengthened university–community engagement by positioning cultural stakeholders as co-educators in the translation process. The field immersion allowed students to appreciate the sociocultural context of Osing literature and provided real-world insights into the complexities of language transfer. The bilingual anthology and accompanying video documentation were disseminated through both print and digital platforms, expanding access to regional Indonesian literature for global audiences. This program demonstrates that student-led literary translation can be a powerful medium for cultural preservation, academic skill-building, and grassroots cultural diplomacy. It highlights the potential of integrating community-based learning with academic programs, offering a sustainable and replicable model for universities aiming to link global engagement with local knowledge. The project also contributes to preserving linguistic diversity and promoting intercultural understanding through education.